2022
DOI: 10.1186/s13071-022-05372-x
|View full text |Cite
|
Sign up to set email alerts
|

Probe-based qPCR as an alternative to modified Knott’s test when screening dogs for heartworm (Dirofilaria immitis) infection in combination with antigen detection tests

Abstract: Background Current recommendations for diagnosis of Dirofilaria immitis infection in dogs rely on the detection of antigen produced largely by adult females coupled with the visualization of microfilariae (mf) in the circulation via a microfilaria detection test (MFDT). It is hypothesized that qPCR assays used in parallel with antigen detection tests will perform better in detecting mf than modified Knott’s test (MK), when combined with antigen detection. This study compares probe-based qPCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The American Heartworm Society recommends both antigen testing and microfilariae testing of all canine samples [33], but microfilariae tests are not routine procedure. Consistent with our own previous results [16,42], antigen and microfilaria testing by qPCR in the present study gave different estimates of prevalence. Antigen tests work well at diagnosing infection with higher numbers of female D. immitis worms but are less sensitive for male-only infection with ≤ 3 females [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The American Heartworm Society recommends both antigen testing and microfilariae testing of all canine samples [33], but microfilariae tests are not routine procedure. Consistent with our own previous results [16,42], antigen and microfilaria testing by qPCR in the present study gave different estimates of prevalence. Antigen tests work well at diagnosing infection with higher numbers of female D. immitis worms but are less sensitive for male-only infection with ≤ 3 females [40].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, antigen tests are more effective at identifying female worms that are > 6 months of age, making infection difficult to diagnosis in dogs aged < 6 months as it takes 50-58 days post-infection for L3 to develop into adults [41]. qPCR is a reliable and specific diagnostic tool for D. immitis [42] and the use of multiple diagnostic tests has been shown to improve diagnostic performance [29,43,44]. Two earlier studies found that qPCR detected a higher prevalence rate than antigen testing alone [29,45], similar to our results as three dogs in the present study were considered to be D. immitis microfilaria positive and NAD before and after ICD.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting if we can improve the potential of the chip on in-chip identification. Moreover, purifiedlife microfilariae isolation and concentration are the device's advantages over other conventional methods (21,22). These might be very impactful for further research.…”
Section: Discussionmentioning
confidence: 99%
“…These may be divided into parasitological techniques for mfs detection in the host’s blood (e.g., fresh blood smear, buffy coat examination, filtration or modified Knott’s test), serological (i.e., enzyme-linked immunosorbent assays (ELISA), rapid immunochromatographic tests (ICT) and molecular approaches (i.e., probe-based quantitative polymerase chain reaction (qPCR), conventional PCR (cPCR), duplex qPCR for the simultaneous detection of both Dirofilaria spp. )), together with fine-needle aspirate (FNA) and histological examination of nodules when present ( 3 , 12 , 17 , 18 ). Serological tests are available as reference laboratory assays and also point-of care (POC) tests ( 3 , 19 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies on the incidence and/or prevalence of Dirofilaria spp. infection in the same canine population have shown differing results according to the diagnostic method adopted ( 15 , 18 , 19 , 30 ). For this reason, diagnosis of animal dirofilariosis must rely on the integration of results from at least two methods in order to reduce the risk of false positives and negatives, as recommended by the AHS ( 24 ).…”
Section: Introductionmentioning
confidence: 99%